The triple, quadruple, and quintuple helix models: A bibliometric analysis and research agenda - Haziman, Zakaria; Muhammad Ashraf, Fauzi; Diyana, Kamarudin; Norazah, Mohd Suki; Mohd Ariff, Kasim (Springer Nature, 2024)
The helix model (triple, quadruple, and quintuple) research has grown drastically in the past decade as a practical approach for establishing new theories and spreading knowledge. Expanding research is being conducted on the underlying causes and effects of the helix model development in knowledge sharing. This study assesses the literature on model helix creation in knowledge sharing through three components of bibliometric analysis (co-citation analysis, bibliographic coupling, and co-word analysis) based on 227 peer-reviewed publications from 1970 to 2022. This literature review integrates thematic groups from different analyses to offer a holistic picture of the current state-of-the-art, designing its main approaches and offering future field trends. These findings are crucial for academics, practitioners, and stakeholders in seeking to improvise the helix model for policymakers by incorporating the helix model into a knowledge-sharing strategy.